The development of the syntax of post-biblical Hebrew - Rabin, Chaim (Studies in Semitic languages and linguistics ;, 2000)
This volume is concerned with a historical development of the syntax of Hebrew in the post-biblical periods, more specifically from the twelfth to the fifteenth centuries as used in non-artistic prose in Southern France and Spain, a period in which the language underwent some fundamental changes and developments. With his superb knowledge of all phases of Hebrew the author portrays and analyses these developments in relation to Biblical and Mishnaic Hebrew. This is a highly original and important contribution to a diachronic description of Hebrew syntax, and undoubtedly a necessary reading for any serious Hebraist and Semitist.